2007
DOI: 10.4028/www.scientific.net/msf.539-543.3335
|View full text |Cite
|
Sign up to set email alerts
|

Stored Energy and Recrystallization Process

Abstract: Stored energy plays a crucial role in recrystallization process. One can distinguish two contributions to this energy. The first one is the elastic energy, connected with residual stresses, i.e., with grain-grain interaction. Another part of the stored energy is due to dislocation density, which is mainly localized inside grains. The latter one is considered as a main driving force of recrystallization. However, the stored energy connected with residual stresses can also have some influence on this process. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The kernel average misorientation (KAM) of a material is proportional to its geometrically necessary dislocation (Koyama et al, 2014b). The higher KAM value of steel B' represents high storage energy, which played a crucial role in the recrystallization process (Baczmanski et al, 2007), steel B showed equiaxed morphology after the subsequent annealing process.…”
Section: Austenite Stabilitymentioning
confidence: 99%
“…The kernel average misorientation (KAM) of a material is proportional to its geometrically necessary dislocation (Koyama et al, 2014b). The higher KAM value of steel B' represents high storage energy, which played a crucial role in the recrystallization process (Baczmanski et al, 2007), steel B showed equiaxed morphology after the subsequent annealing process.…”
Section: Austenite Stabilitymentioning
confidence: 99%
“…Stored energy plays an important role in the recrystallization process, and its contributions can be categorized as elastic energy and dislocation density. Elastic energy relates to residual stress, which is characterized by grain-to-grain interactions, while dislocation density is mainly confined inside the grains [22].…”
Section: • Microstructuresmentioning
confidence: 99%
“…It was found that the stored energy in many AM materials is mainly due to the dislocation density, as the stored energy in the form of residual stress is not on a high enough level to induce recrystallization. Martensitic transformations are sometimes considered as a method to increase the dislocation density inside the material [22]. Lath martensites are typically associated with high dislocation densities, as they can accommodate high strains due to the diffusionless martensitic transformation [24].…”
Section: Residual Stressmentioning
confidence: 99%
“…The stored energy is a fraction of the energy supplied by the external load during deformation; the rest is released as heat [7,8]. The driving force for recrystallization is generally described as the driving pressure [1,[9][10][11]:…”
Section: Introductionmentioning
confidence: 99%
“…The stored energy is a fraction of the energy supplied by the external load during deformation; the rest is released as heat [7,8]. The driving force for recrystallization is generally described as the driving pressure [1,9-11]: where α is a constant (typically in the order of 0.5), G is the shear modulus, b is the Burgers vector and ρ is the dislocation density [1,5,12]. The local stored energy can be estimated experimentally by investigating the lattice distortion by synchrotron X-ray diffraction with suitable spatial resolution or electron microscopy, while measuring the heat released from the deformed sample during annealing using calorimetry gives the global stored energy [3,8,13].…”
Section: Introductionmentioning
confidence: 99%